Peran Pendidikan Kewiraushaaan dan Self Efficacy Terhadap Intensi Berwirausaha Mahasiswa - Eza Kurniati; Tri Kurniawati (Universitas Negeri Padang, 2020)
The purpose of researche is to know the role of entrepreneurship education’and self efficacy on entrepreneurial intentions student economic faculty of Padang State University. Research used causal asositive the population the research were students Economic Faculty of Padang State University. Number of samples were decided base on hair et. As many as 86 people and chosen stratified proportional Random Sampling using. Data are used is primer data were provided through questionnaire shared to students economic faculty of State University of Padang based on predetermined criteria. Analysis metho used is multiple using by spss 20. The results this research shows (1) entrepreneurship education and self efficacy any significant effect to entrepreneurial intentions, (2) entrepreneurship education have no significant affect on entrepreneurial intentions, (3) self efficacy have significant effect on entrepreneurial intentions. Keywords: enterpreneurship education, self-efficacy, entrepreneurial intentions